Idealism, Realism and the Obama’s Foreign Policy towards the Arab Spring 2011 - Chahrazed BOUAISSI, Ahlam BENBOUZID (My University, 2018)
IV ABSTRACT This thesis deals with the Arab Spring as a process of profound political change in the Arab world, previously the only major world area where dictatorship endured unchallenged for decades. While in different countries of the Arab world mass protests in 2011 constrained rulers to hand over power, however; other dictator administrations have – in spite of political and economic pressure – so far possessed the capacity to stay in power. The Arab Spring influenced every country in the region very differently. Six countries are chosen for the analysis. The American President Barack Obama and his top diplomats’ performances respond to each country differently according to U.S. national interests, and its key objectives in the Middle East region. The motivation behind this thesis is to understand the Obama Doctrine and set up a clearer meaning of what it is by contextualizing it through the perspectives of other presidential tenets, the schools of idealism and realism. In addition to that, this thesis aims to set up specific tenets of the Obama Doctrine, as well as recognize the contradictions existed inside the Obama Doctrine that appeared when responding to the Arab Spring. We will then use Obama’s arc of disenchantment to explain how the Arab Spring changed the Obama Doctrine’s way of decision making.
Keywords: Idealism, Realism - Obama’s Foreign Policy towards- Arab Spring 2011